Eksistensi Kematian sebagai Akhir: Thanatos dan Eros dalam Ziarah Karya Iwan Simatupang (Perspektif Psikoanalisis Freudian) - Rahayu, Titin Puji; Atikurrahman, Moh.; Alfin , Jauharotin (MIMESIS, 2024)
This article explores personality dynamics in Indonesian literature by taking the theme of death in the novel Ziarah by Iwan Simatupang (1969). The concept of 'Thanatos and Eros' from Freudian psychoanalytic research is understood as the relationship between instincts in human behavior, which are described as conflicting settings, namely the death instinct and the life instinct. This research uses a qualitative description method and a content analysis method in the form of presenting data in the form of words and sentences taken from the novel Ziarah by Iwan Simatupang (1969) on the aspects of Thanatos (death instinct), eros (life instinct) and anxitas (anxiety). The research techniques used are literature review, note-taking, and data processing techniques. Thus, research into personality dynamics in the novel Ziarah by Iwan Simatupang obtained six data on Thanatos (death instinct), five data on eros (life instinct), and one data on anxitas (anxiety). Thanatos (death instinct) data emphasizes the death instinct in the form of aggression and suicidal actions in the Painter character, the Young and Old Operative character, and the Mayor character. The eros data (life instinct) emphasizes the sexual instinct in the painter's characters and the non-sexual instinct (lamentation poetry) in fulfilling physical needs such as feelings of hunger, thirst, work, and others. Anxiety data emphasizes the anxiety of death in the painter's character.